2016
DOI: 10.18203/2394-6040.ijcmph20162041
|View full text |Cite
|
Sign up to set email alerts
|

Health seeking behaviour among post-menopausal women: a knowledge, attitude and practices study

Abstract: Background: Ageing women suffer problems associated with senility along with that of the reproductive tract changes. Unless the woman is treated as a whole, her problem is actually not addressed. With this background, the present study was undertaken with the following objectives: to identify the major health problems of postmenopausal women, to determine the level of knowledge, attitude and practices of postmenopausal women in terms of seeking Health care facilities for their problems and to determine the uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 4 publications
2
16
1
Order By: Relevance
“…11 The study findings were muscle and joint pain 95% (p<0.0001), parts of the body feeling numb or tingling 93.3% (p<0.0001), difficulty in sleeping 86.5% (p<0.0001), irritability 85.8% (p<0.0001) and these rates were significantly higher than those reported in the current study, but the prevalence of muscle and joint pain (p<0.14) were similar to the study findings vasomotor symptoms like hot flushes 46.7% (p<0.0013) and night sweats 50% (p<0.032) reported from the study based. 12,13 The study findings concur with Global and Asian study findings regarding more prevailing symptoms as physical than vasomotor symptoms Kulkarni et al women in late menopause, who had induced menopause and premature menopause was affected by severe symptoms. There was a significant positive correlation between postmenopausal symptoms and age.…”
Section: Discussionsupporting
confidence: 86%
“…11 The study findings were muscle and joint pain 95% (p<0.0001), parts of the body feeling numb or tingling 93.3% (p<0.0001), difficulty in sleeping 86.5% (p<0.0001), irritability 85.8% (p<0.0001) and these rates were significantly higher than those reported in the current study, but the prevalence of muscle and joint pain (p<0.14) were similar to the study findings vasomotor symptoms like hot flushes 46.7% (p<0.0013) and night sweats 50% (p<0.032) reported from the study based. 12,13 The study findings concur with Global and Asian study findings regarding more prevailing symptoms as physical than vasomotor symptoms Kulkarni et al women in late menopause, who had induced menopause and premature menopause was affected by severe symptoms. There was a significant positive correlation between postmenopausal symptoms and age.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, Khan et al suggested that to deal with menopausal problems, majority of the women in urban areas said that a doctor should be consulted (52.7%) whereas majority in rural areas either said that they did not know what could be done (47.9%) or traditional or home-based measures should be resorted to (40.0%). 17 43.4% of the rural women had never visited any health facility for menopausal problems as compared to 26.4% in urban areas. Those women who never visited any preferred health facility, a majority gave reasons such that it was far away, that they did not trust the facility, there was no one to accompany them or they preferred resorting to home-based remedies for their ailments.…”
Section: Discussionmentioning
confidence: 94%
“…Most of the postmenopausal women feel that, the medical problems experienced in that phase of life are due to old age. 3 The present study was undertaken to assess the health seeking behaviour among the postmenopausal women.…”
mentioning
confidence: 99%